2006
DOI: 10.1061/(asce)0733-9372(2006)132:6(653)
|View full text |Cite
|
Sign up to set email alerts
|

Multiyear Temporal Changes in Chlorinated Solvent Concentrations at 23 Monitored Natural Attenuation Sites

Abstract: Long-term ͑e.g., 5-15 years͒ groundwater concentration versus time records were compiled from 47 near-source zone monitoring wells at 23 chlorinated solvent sites ͑52 total records͒. Chlorinated volatile organic compound ͑CVOC͒ concentrations decreased significantly in most of the 52 temporal records, with a median reduction in concentration of 74%. A statistical method based on a Mann-Kendall analysis also showed that most sites had statistically significant decreasing concentration trends over time. Median p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 11 publications
4
47
0
Order By: Relevance
“…In contrast, analytical solutions can be highly efficient, but are generally limited to simpler domains with homogeneous and isotropic properties. This behavior has been observed in both field (e.g., McGuire et al 2006;Newell et al 2006) and numerical modeling studies (e.g., Parker and Park 2004). Although the source concentration response to source mass reduction can be highly variable (e.g., Parker and Park 2004), Falta et al (2005) describes a special case where source concentration is linearly proportional to source mass, and both source mass and source concentration simultaneously exhibit exponential decay with time.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In contrast, analytical solutions can be highly efficient, but are generally limited to simpler domains with homogeneous and isotropic properties. This behavior has been observed in both field (e.g., McGuire et al 2006;Newell et al 2006) and numerical modeling studies (e.g., Parker and Park 2004). Although the source concentration response to source mass reduction can be highly variable (e.g., Parker and Park 2004), Falta et al (2005) describes a special case where source concentration is linearly proportional to source mass, and both source mass and source concentration simultaneously exhibit exponential decay with time.…”
Section: Introductionmentioning
confidence: 76%
“…An example of the latter is the study by Falta et al (2005) who developed an analytical source function for NAPL source dissolution and remediation. In a review of DNAPL sites undergoing natural attenuation, Newell et al (2006) reported downgradient source concentration half-life values from as low as 0.7 years for tetrachloroethylene (PCE) to constant (or even increasing) concentrations for trichloroethylene (TCE). This behavior has been observed in both field (e.g., McGuire et al 2006;Newell et al 2006) and numerical modeling studies (e.g., Parker and Park 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluation of long-term monitoring records from individual monitoring wells indicates that linear and first-order models provide similar quality fits to the data (Newell et al 2006;McHugh et al 2011). For the purpose of estimating the long-term attenuation rate, the statistical methods for the two models are almost identical.…”
Section: Use Of Regression Analysis To Estimate Attenuation Ratesmentioning
confidence: 93%
“…For example, Newell et al 84 present data from 23 chlorinated solvent MNA sites monitored for 5-15 years. The survey showed a median reduction in contaminant concentration of 74%.…”
Section: Chlorinated Solvent Plumesmentioning
confidence: 97%